The Wasteful Son - Dania, Deji (Literamed Publications Nigeria Limited, 2009)
In another country,the wasteful son foolishly spends all he has and becomes a poor man, and keeper of pigs. The taste of pigs food makes him choose to return to a home he had neglected,but he wonders if his rich father would ever forgive him.
Keywords: Christianity; Bible Stories; Religion